Stres dan Kualitas Tidur Caregiver dalam Merawat Pasien Skizofrenia di Poliklinik RSJ Bina Karsa Kota Medan - Roxsana Devi Tumanggor; Yuli Marhamah (Jurnal Keperawatan Muhammadiyah, 2021)
Family caregiver is the primary care provider for family members with spesific illness. It is often the caregiver experiences stress and sleep disturbances during the caregiving process. This research is a descriptive study which aims to analyze the stress and sleep quality of caregivers in caring for schizophrenia patients at the Polyclinic of the Bina Karsa Psychiatric Hospital / RSJ Bina Karsa Kota Medan. The study population was 442 caregiver patients with schizophrenia who accompanied the patient routine control from April to May 2019.  40 samples were involved with purposive sampling technique.  The criteria of caregiver for schizophrenia patients were the family caregiver (father, mother, children, siblings, husband/wife etc.), provide care for 1-4 years, lived in Medan and patients is the recurrent patients. The instruments in this study were a demographic data questionnaire, a DASS 42 (Depression Anxiety Stress Scale) questionnaire and an SQQ (Sleep Quality Questionnary) questionnaire. The collected data were then analyzed by descriptive test, Annova test, and Kruskal Walis test. Based on the results of this study, the majority of respondents experienced mild stress 28 people (70%) with an average length of stay of 1 year and 3 months. For the quality of sleep experienced by the caregiver, data was obtained that 24 respondents (60%) experienced poor sleep quality and only 2 respondents (5%) experienced good sleep quality. In 2 respondents who had good sleep quality, the average length of stay was 3 years, 24 respondents had poor sleep quality, the average length of stay was 2 years 5 months, 14 respondents had adequate sleep quality, and the average length of stay was 1 year 10 months. The results of this study can be used as basic data for further assessment of caregivers who are often not a priority in health service policies.